Ferrous to Ferric Transition in Fe‐Phthalocyanine Driven by NO2 Exposure. Issue 10 (25th January 2021) - Cojocariu, Iulia; Carlotto, Silvia; Sturmeit, Henning Maximilian; Zamborlini, Giovanni; Cinchetti, Mirko; Cossaro, Albano; Verdini, Alberto; Floreano, Luca; Jugovac, Matteo; Puschnig, Peter; Piamonteze, Cinthia; Casarin, Maurizio; et al.
Abstract: Due to its unique magnetic properties offered by the open‐shell electronic structure of the central metal ion, and for being an effective catalyst in a wide variety of reactions, iron phthalocyanine has drawn significant interest from the scientific community. Nevertheless, upon surface deposition, the magnetic properties of the molecular layer can be significantly affected by the coupling occurring at the interface, and the more reactive the surface, the stronger is the impact on the spin state. Here, we show that on Cu(100), indeed, the strong hybridization between the Fe d‐states of FePc and the sp‐band of the copper substrate modifies the charge distribution in the molecule, significantly influencing the magnetic properties of the iron ion. The Fe II ion is stabilized in the low singlet spin state ( S =0), leading to the complete quenching of the molecule magnetic moment. By exploiting the FePc/Cu(100) interface, we demonstrate that NO2 dissociation can be used to gradually change the magnetic properties of the iron ion, by trimming the gas dosage. For lower doses, the FePc film is decoupled from the copper substrate, restoring the gas phase triplet spin state ( S =1). A higher dose induces the transition from ferrous to ferric phthalocyanine, in its intermediate spin state, with enhanced magnetic moment due to the interaction with the atomic ligands. Remarkably, in this way, three different spin configurations have been observed within the same metalorganic/metal interface by exposing it to different doses of NO2 at room temperature. Abstract : By exploiting the FePc/Cu(100) interface, the possibility to control, via nitrogen dioxide (NO2 ) dissociation at the interface, the magnetic properties of the chelated ion the FePc array is demonstrated. Three different spin configurations have been stabilized within the same metalorganic/metal interface.